Come to grief - Francis, Dick (G.P. Putnam's Sons, 1995)
When ex-jockey Sid Halley becomes convinced that one of his closest friends--and one of the racing world's most beloved figures--is behind a series of shockingly violent acts, he faces the most troubling case of his career.